Reconstruction of simple parts using FDM technology - Dömötör, Csaba (Design of Machines and Structures, 2023)
This article shows the experiences of component reconstruction supported by FDM 3D printing through a few examples. It presents the profile copying technique that can be used as an alternative to traditional measuring methods and 3D scanners for relatively complicated parts.